Improving Students' Ability in Speaking Through Role Play Technique: A Classroom Action Research on the Eighth Grade Students of SMP Negeri I Serawai in Academic Year 2014/2015 - Andreas Andre; Urai Salam; Iwan Supardi (Kirana Publisher (KNPub), 2023)
Role-play in learning leads to a teaching-learning activity more focused on students. This research aimed to investigate the improvement of the speaking aspect in the classroom. This research was Classroom Action Research (CAR) in two cycles for 25 eighth-grade students of SMPN 1 Serawai in the academic year 2014–2015. The results showed that the mean fluency score increased from 24.20 in the first cycle to 28.88 in the second cycle. This shows that speaking is sometimes hesitant. The pronunciation has risen from 24.20 to 30.60, which indicates student’s pronunciation is in the category of not foreign accents and occasional mispronunciation but does not interfere with the understanding. The grammar component was 9.76, increasing to 13.88, indicating that the student’s grammar has occasional errors showing interference control and some pattern but no weakness that causes misunderstanding. The result of the observation and the student assessment also showed that there were improvements in the student's participation during teaching and learning activities. The researcher suggests that teachers can use this technique to help students improve their speaking and other English skills.